Determinants of Islamic Home Financing Product Selection among Lower Income Group in Kuala Lumpur, Malaysia - Maamor, Selamah; Rahman, Nurul Labanihuda Abdull; Hamed, Abu Bakar (International Journal of Economics and Financial Issues, 2016)
Recently, affordability of housing in Malaysia has becoming crucial issue especially in big cities due to economic growth and high living cost. Hence, these studies aim to investigate the factors that influence customer in Kuala Lumpur in selecting Islamic home financing product. In this study, we assume the factors that will influence customer selection for Islamic home financing are attitude, subjective norms, pricing, religious obligation, government intervention and service provision. This study used samples of 150 respondents who had an experiences purchasing house in Kuala Lumpur. This study employed Pearson Correlation and Multiple Regression method to achieve the objective. Finding shows that there is a significant relationship between attitude, religious obligation, and service provision towards Islamic homes financing selection. Therefore, it is recommend that the Islamic financial provider to improve several factors is including but not limited to marketing, operation and customer service in order to attract customers to purchase Islamic home financing product. Most importantly, all the products offered must in line with Shariah in terms of the content of the product, the contract and also the way it is delivered to the customer. Keywords: Islamic home financing, Attitude, Subjective norm, Pricing, Religious obligation, Government intervention and Service provision JEL Classifications: R31, G21, E210